Effects of innovation capability and environmental dynamism on the relationship between entrepreneurial leadership and innovation performance in the SMEs service industry - M. Al-Sharif, Abdulrahman; Hareeza Ali, Mass; Jaharuddin, Nor Siah; Abdulsamad, Akram (Human Resource Management Academic Research Society, 2023)
This paper explores the link between entrepreneurial leadership (EL) and innovation performance (IP) in the service industry. Using the resource-based view (RBV) and dynamic capabilities view (DCV) as theoretical foundations, the study examines the mediating role of innovation capability (IC) and the moderating role of environmental dynamism (ED) in this relationship. A survey of 321 middle-level managers in the SME service sector was conducted to test the hypotheses, employing SMART-PLS structural equation modeling. Results show that EL directly and indirectly affects IP through IC mediation, but no evidence was found for the moderating role of ED. This research contributes to the understanding of how entrepreneurial leaders influence innovation performance and highlights the importance for SME owners and managers to foster and apply entrepreneurial leadership skills.